PROSPECTS FOR THE DEVELOPMENT AND INTEGRATION OF MAGNESIUM BINDING MATERIALS INTO MODERN BUILDING TECHNOLOGIE - Malyi, Yevhenii (Municipal economy of cities. Series: «Economy science», 2025)
This study highlights the prospects for the development and integration of magnesian materials into modern construction technologies. Magnesian binders exhibit a rapid setting time, low shrinkage, good adhesion to surfaces, and resistance to aggressive environments. They outperform Portland cement in terms of strength, thermal stability, and crack resistance, while their production requires less energy. During the hardening process, they absorb CO₂, reducing greenhouse gas emissions and contributing to climate change mitigation. This unique feature makes them a promising material for sustainable and eco-friendly construction practices. Magnesian materials are increasingly used in a variety of applications, including thermal insulation boards, fire-resistant coatings, decorative panels, and even in 3D printing for construction. In China, they are particularly popular due to their low cost and the abundant availability of magnesite. In the United States and Canada, magnesian binders are widely applied in fire-resistant structures, offering better durability and safety compared to traditional materials. In Ukraine, however, magnesian binders are not produced on an industrial scale, despite the country’s large reserves of dolomite, which is a primary raw material for their production. The development of this industry could significantly reduce the import of expensive cement, while also decreasing the environmental burden associated with cement production. The use of magnesian binders could become a sustainable alternative to traditional cement in construction, offering lower energy consumption, improved quality of building structures, and the ability to implement more modern and advanced technologies. Nevertheless, the widespread adoption of magnesian binders is currently hindered by a lack of investment, research, and technological advancement. Without significant state support and targeted investments in research and development, the market will remain dependent on imported analogs, and the potential of this promising material will not be fully realized. Magnesian binders could play a crucial role in the development of sustainable and energy-efficient construction solutions, contributing to the global efforts to reduce carbon footprints. The future of this technology depends on continued scientific research, the implementation of innovative approaches, and the expansion of production capacities. As the construction industry moves toward more eco-conscious practices, magnesian materials could become integral to realizing the goals of green architecture and energy-efficient building design.